Non-equilibrium dynamics of fluctuations in an ultra-cold atomic mixture - Hegde, Apoorva Anant; Ott, Robert; Xia, Andy Xiyuan; Kasper, Valentin; Berges, Jürgen; Jendrzejewski, Fred (Arxiv, 2022)
We investigate an ultra-cold mixture of Bose gases interacting via spin-changing collisions by studying the dynamics of spin fluctuations. The experimental implementation employs $^{23}$Na and $^{7}$Li atoms, which are prepared out of equilibrium across a wide range of initial conditions. We identify three regimes in the dynamics of the system for different initial states: a long-lived metastable regime, an instability range with strong growth of fluctuations, and a fast relaxing regime approaching thermal equilibrium. Theoretical modelling of the data allows us to reconstruct effective potentials which characterize the different dynamical regimes of the system.